LUPEOL VALIDATION AND QUANTIFICATION IN HETEROPOGON CONTORTUS (L.) BEAUV. (SPEAR GRASS) THROUGH HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY - Kaur, Navjot; Gupta, Raghbir Chand (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This is aimed to study the chromatographic evaluation of triterpenoid, i.e., lupeol from methanolic extracts of leaves, stem, and inflorescence of Heteropogon contortus. Methods: The high-performance thin-layer chromatography (HPTLC) densitometry determination of lupeol was performed using optimized mobile phase toluene:methanol:formic acid (7:3:0.3 v/v) with a derivatization of freshly prepared anisaldehyde-sulfuric acid. For densitometry measurements, the plates were scanned at 530 nm absorbance/reflectance wavelength. Quantification of lupeol marker compound in H. contortus leaves, stem, and inflorescence is estimated using 2-12 Î¼g/spot. Results: The appearance of light purple bands on the chromatograms confirmed the lupeol component in plant samples. Further, the confirmation of the compound is done from the densitometric scanning by comparing Î»max values. From this, it is reported that lupeol is present in leaf samples, i.e., 10 mg/g of dry wt., while in rest of the two samples, it is found absent. Conclusion: The leaves of H. contortus (spear grass) are a good source of lupeol and can be used as an alternate natural source to synthesize herbal drugs to control cancer and other anti-inflammatory agents. The presently selected HPTLC is validated and most accurate for the quantification and identification of lupeol present in the selected plant. The leaves of the species which are rich in lupeol can be used in pharmaceutical industry.